Effect of ph solution on the water absorbency of superabsorbent polymer composite - Ayuni Athirah, Azman (2013)
Nowadays, superabsorbent polymer composite (SAPC) has been world widely known because of its capacity in contributing beneficial applications in daily life. In this study, Poly Oil Palm Empty Fruit Bunch-co-Acrylamide superabsorbent polymer composite (OPEFB-AM-SAPC) was synthesized by solution polymerization of the Acrylamide (AM) monomer onto OPEFB fibre using Ammonium Persulphate (APS) and N, Nmethylene bisacrylamide (MBA) which act as an initiator and crosslinker, respectively.The effects of different pH solution and filler amount towards water absorbency have been identified by studying the optimum condition of each parameter towards water absorbency capacity of polymer. For a parameter of pH solution, the maximum water absorbency was observed at pH 4 for fixed filler amounts. Meanwhile, for the effect of different filler loading, the optimum water absorbency of OPEFB-AM-SAPC was achieved at 2.5 wt% of filler loadings which reveals the well-organized loosely polymeric structure with multiple porous structures that suitable for penetration of water into the polymeric network. These multiple porous structures lead for high water uptake within the network. On the other hand, the characterizations of OPEFB-SAPCs have been carried out by using Fourier Transform Infrared Spectroscopy (FTIR), Thermogravimetric Analysis (TGA) and Field Emission Scanning Electron Microscopy (FESEM). The thermogravimetry analysis result of OPEFB-SAPC at 2.5% filler loading indicate that the SAPC shows a three stage degradation, which unlike the dense unorganized rigid structure been exhibited by the 12.5 wt% filler loading. Meanwhile, FTIR analysis shows OPEFB-SAPC (2.5 wt %) has sharp peak of bonding curves compared to OPEFB-SAPC (12.5 wt%).